A Case Study Exploring the Role of Design in Maturing University-Developed Technology. (May 2022) - Mesa, D.; Tan, L.; Ranscombe, C.
Abstract: Universities struggle to commercialise scientific research. However, designers can help scientists bridge the research-market gap in different ways. Although the value design can bring to science is understood, how design outputs deliver value to scientific research remains unexplored. Our paper reports findings from a designer-scientist collaboration developing a graphene-based water desalination technology. By reflecting on this case study, we found that design outputs serve different purposes in developing technology and assist in progressing technology maturation efficiently.